Effects of 3% Boric Acid Solution on Cutaneous Candida albicans Infection and Microecological Flora Mice - Liu, Qing; Liu, Zhao; Zhang, Changlin; Xu, Yanyan; Li, Xiaojing; Gao, Hongqi (Frontiers in Microbiology, 2021)
To determine the effect of 3% boric acid solution on cutaneous infections with Candida albicans (CA) in mice and its effect on skin microflora. Female mice were divided into three groups, with 18 mice in each group. Two injection sites were randomly selected, and 0.1 mL of CA mycelium suspension was injected into the epidermis and dermis of the back of mice. Group N was treated with sterile water for injection (SWFI). We observed the clinical manifestations, fungal fluorescence microscopic examination and colony count. Group B were hydropathically compressed with 3% boric acid solution for 30 minutes every 12 hours. Group M was treated with SWFI, and group N was not treated. One week later, each group was observed with naked eyes, and skin samples were collected. The effect of boric acid on skin microflora was measured using Internal Transcribed Spacer Identification (ITS) and 16S rRNA genes. There were no significant changes in group M. In group B, the degree of skin injury was alleviated, the wounds healed markedly, and the exudate amount decreased. The effective rate of group B (83%) was significantly higher than that of group M (25%) (P < 0.05). The relative average abundance of Candida (P < 0.0001) and CA (P < 0.05) in group B was significantly lower than that in group M. Compared with group M, the microbial richness of group B changed little, but the diversity decreased. The flora structure of group B was significantly different from that of group M, but like that of group N. In group B, the abundance of Proteobacteria (P < 0.001), Enterobacteriaceae (P < 0.001), and Escherichia-Shigella (P < 0.001) was significantly greater, and the abundance of Firmicutes (P < 0.001), Staphylococcaceae (P < 0.001), and Staphylococcus (P < 0.001) were significantly lower. The 3% boric acid solution significantly reduced the symptoms of skin infection with Candida albicans. It inhibited the growth of Candida albicans and CA, reduced the diversity of skin microorganisms, increased the abundance of Proteobacteria, Enterobacteriaceae, Escherichia-Shigella, and reduced the abundance of Firmicutes, Staphylococcaceae, Staphylococcus.